Prophylactic administration of tranexamic acid combined with thromboelastography-guided hemostatic algorithm reduces allogeneic transfusion requirements during pediatric resective epilepsy surgery: A randomized controlled trial - Zhang, Ting; Feng, Hua; Xiao, Wei; Li, Jingsheng; Liu, Qinghai; Feng, Xuexin; Qi, Dezhou; Fan, Xiaotong; Shan, Yongzhi; Yu, Tao; Zhao, Guoguang; Wang, Tianlong (Frontiers in Pharmacology, 2022)
Background: Intraoperative bleeding and allogeneic transfusion remain common problems in pediatric resective epilepsy surgery. Tranexamic acid (TXA) is a widely recommended antifibrinolytic drug that reduces blood loss and transfusion requirements for bleeding patients. Thromboelastography (TEG)-guided hemostatic algorithm is commonly used in bleeding management. This trial was designed to validate the efficacy of a multimodal coagulation therapy involving continuous TXA infusion with TEG-guided hemostatic algorithm in reducing allogeneic exposure risk in pediatric resective epilepsy surgery. Methods: Eighty-three children undergoing resective epilepsy surgery were randomized into a treatment group (Group T; n = 42) and a control group (Group C; n = 41). Group T received prophylactic TXA (10 mg/kg followed by 5 mg/kg/h) with TEG-guided hemostatic algorithm, whereas Group C received conventional coagulation management. The primary outcome was allogeneic transfusion rate during surgery, and the secondary outcomes were intraoperative blood loss, incidence of postoperative seizures, and thromboembolic events during hospitalization. Results: The incidence of intraoperative allogeneic transfusion reduced by 34.7% with the use of a multimodal coagulation therapy (19.0% in Group T vs. 53.7% in Group C; RR 0.355, 95% CI 0.179–0.704; p = 0.001). This was mainly triggered by a significant reduction (44.1%) in intraoperative plasma transfusion (7.1% in Group T vs. 51.2% in Group C; RR 0.139, 95% CI 0.045–0.432; p = 0.000). The risk of intraoperative RBC transfusion was lower in Group T than in Group C, but the difference was not statistically significant (14.3% in Group T vs. 29.3% in Group C; RR 0.488, 95% CI 0.202–1.177; p = 0.098). No platelets were transfused in both groups. Further, 19 (45.2%) patients in Group T received fibrinogen concentrates guided by TEG data, whereas 1 (2.4%) patient in Group C received fibrinogen concentrates empirically. There were no significant differences in estimated blood loss and postoperative seizures between the two groups, and no thromboembolic events were observed after surgery. Conclusion: Prophylactic administration of TXA combined with TEG-guided hemostatic algorithm can be an effective multimodal coagulation strategy for reducing allogeneic transfusion requirements during pediatric resective epilepsy surgery. Clinical Trial Registration:www.chictr.org.cn/index.aspx, identifier ChiCTR1800016188.